Carbon footprints of Indian food items - Pathak, Himanshu; Jain, Niveta; Bhatia, Arti; Patel J; Aggarwal, Pramod K. (Elsevier, 2010)
Carbon emission occurs during various stages of life cycle of food products. Greenhouse gases (GHG) emission from 24 Indian food items showed that animal food products (meat and milk) and rice cultivation mostly contributed to methane (CH4) emission, while food products from crops contributed to emission of nitrous oxide (N2O). Emission of CO2 occurred during farm operations, production of farm inputs, transport, processing and preparation of food. The GHG emission during the life cycle of cooked rice was 2.8 times the GHG emission during the life cycle of chapatti, a product of wheat flour. Mutton emitted 11.9 times as much GHG as milk, 12.1 times fish, 12.9 times rice and 36.5 times chapatti. As Indians mostly consume fresh foods produced locally, 87% emission came from food production followed by preparation (10%), processing (2%) and transportation (1%). For a balanced diet (vegetarian) an adult Indian man consumed 1165 g food and emitted 723.7 g CO2 eq. GHG d−1. A non-vegetarian meal with mutton emitted GHG 1.8 times of a vegetarian meal, 1.5 times of a non-vegetarian meal with chicken and an ovo-vegetarian meal and 1.4 times a lacto-vegetarian meal. Change in food habit thus could offer a possibility for GHG mitigation.